Metabolic Regulation of Organic Acid Biosynthesis in Actinobacillus succinogenes - Zhang, Wenming; Yang, Qiao; Wu, Min; Liu, Haojie; Zhou, Jie; Dong, Weiliang; Ma, Jiangfeng; Jiang, Min; Xin, Fengxue (Frontiers in Bioengineering and Biotechnology, 2019)
Actinobacillus succinogenes is one of the most promising strains for succinic acid production, however, the lack of efficient genetic tools for strain modiﬁcation development hinders its further application. In this study, a markerless knockout method for A. succinogenes using in-frame deletion was first developed. The resulting ΔpﬂA (encode pyruvate formate lyase 1-activating protein) strain displayed distinctive organic acid synthesis capacity under different cultivation modes. Additional acetate accumulation was observed in the ΔpﬂA strain relative to that of the wild type under aerobic condition, indicating that acetate biosynthetic pathway was activated. Importantly, pyruvate was completely converted to lactate under anaerobic fermentation. The transcription analysis and enzyme assay revealed that the expression level and specific activity of lactate dehydrogenase (LDH) were significantly increased. In addition, mRNA expression level of ldh was nearly increased 85-fold than that of wild type strain during aerobic-anaerobic dual-phase fermentation, resulting in 43.05 g/L lactate. These results demonstrate that pflA plays an important role in the regulation of C3 flux distribution. The deletion of pflA leads to the improvement of acetic acid production under aerobic condition and activates lactic acid biosynthesis under anaerobic condition. This study will help elaborate the mechanism governing organic acid biosynthesis in A. succinogenes.